2019
DOI: 10.1016/j.carbon.2018.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of soot particles in a diffusion flame

Abstract: The evolution of the internal structure of soot particles was studied in a coflow diffusion flame. Soot particles from the flame were imaged using high resolution transmission electron microscopy. An algorithm to quantify the nano-structure of the particles was extended to study the radial distribution of fringes within the particles. The approximate size of the molecules in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 56 publications
8
42
0
1
Order By: Relevance
“…10a,c). This finding has been also reported by many other researchers for a variety of diffusion flames [e.g., 5,23,44]. The averaged soot aggregate sizes in the 60% C 2 H 4 diffusion flame are greater than those in the 50% C 2 H 4 diffusion flame.…”
Section: Figsupporting
confidence: 88%
“…10a,c). This finding has been also reported by many other researchers for a variety of diffusion flames [e.g., 5,23,44]. The averaged soot aggregate sizes in the 60% C 2 H 4 diffusion flame are greater than those in the 50% C 2 H 4 diffusion flame.…”
Section: Figsupporting
confidence: 88%
“…This finding is consistent with a HRTEM analysis by Botero et al, who estimated the number of rings of a fringe found in soot particles based on the fringe length. 91 Furthermore, 18% of the structures include one or more rings with an odd number of C-atoms, leading to a stress in the graphitic plane and as a result to a more bend structure. This finding is consistent with other modeling studies, [92][93][94] as well as a recent atomic force microscopy study by Schulz et al 40 on soot precursors in the inception regime, showing that odd-numbered rings are found in nascent soot particles.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster structures show a core-shell structure in which stacked larger molecules dominate the core of the cluster. Recently, the first experimental work analysing molecule size with respect to soot particle radius at different soot maturities was published [71]. Using high resolution transmission electron microscopy, it was M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%